Bacterial communities in penile skin, male urethra, and vaginas of heterosexual couples with and without bacterial vaginosis - Zozaya, Marcela (Microbiome, 2016)
BACKGROUND: The epidemiology of bacterial vaginosis (BV) suggests it is sexually transmissible, yet no transmissible agent has been identified. It is probable that BV-associated bacterial communities are transferred from male to female partners during intercourse; however, the microbiota of sexual partners has not been well-studied. RESULTS: Pyrosequencing analysis of PCR-amplified 16S rDNA was used to examine BV-associated bacteria in monogamous couples with and without BV using vaginal, male urethral, and penile skin specimens. The penile skin and urethral microbiota of male partners of women with BV was significantly more similar to the vaginal microbiota of their female partner compared to the vaginal microbiota of non-partner women with BV. This was not the case for male partners of women with normal vaginal microbiota. Specific BV-associated species were concordant in women with BV and their male partners. CONCLUSIONS: In monogamous heterosexual couples in which the woman has BV, the significantly higher similarity between the vaginal microbiota and the penile skin and urethral microbiota of the male partner, supports the hypothesis that sexual exchange of BV-associated bacterial taxa is common. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40168-016-0161-6) contains supplementary material, which is available to authorized users.